Microwave-assisted extraction of lipid from Nannochloropsis sp. microalgae using brine solution - Zghaibi, Nour A. T. (2019)
Microwave-assisted extraction (MAE) technique is considered a potential method for microalgal lipid extraction, but the usage of harmful and non-polar solvents limit its sustainability. Toward attaining an eco-friendly process, a green solvent, brine (NaCl solution) was proposed as MAE solvent to extract lipids from Nannochloropsis sp. microalgae. The main aim of this study is to maintain a high lipid extraction from Nannochloropsis sp. microalgae via MAE-green solvent technique. The solvent for the MAE, brine solution (NaCl dissolved in water) concentration and the microwave parameters were investigated prior to the optimization study. The extraction kinetic was also studied to verify the extraction mechanism using extraction models including Fick’s Law, First and Second- order Rate Law and Patricelli mathematical model. Finally, the product and by- products from the optimized MAE-brine technique was compared to the conventional extraction methods, namely Soxhlet and Bligh and Dyer (B&D).